Internações por condições cardiovasculares sensíveis à atenção primária no Estado do Paraná - Lentsck, Maicon Henrique (2013)
Access and quality in primary health care are key elements in all health systems worldwide in the wake of the increasing challenge of cardiovascular diseases. Hospitalizations due to cardiovascular conditions sensitive to primary health care in the state of Paraná, Brazil, between 2000 and 2011 are analyzed. Current investigation employs ecological-type time series derived from information provided by the SUS´s Hospital Information System. Population consisted of people between 35 and 74 years old who were hospitalized mainly for arterial hypertension, angina, heart conditions and cerebrovascular diseases classified in the Brazilian list of conditions requiring primary health care. Demographic data and population estimates for each year were used while hospitalization rates were constructed by the variables cause, gender, age, county grouped by regional health units with 10,000 inhabitants. Population of the Family Health Strategy (FHS) per regional health units was calculated from data base information of the Basic Health Care Department of the Ministry of Health. Data were processed by polynomial regression models for trends and by Pearson-Spearman´s linear co-relation coefficient for the co-relationship between rates and FHS coverage. Hospitalization rates due to sensitive cardiovascular conditions decreased in the state of Paraná, Brazil (r2=0.96; p<0.001) between 2000 and 2011. Cardiovascular causes decreased hospitalization due to arterial hypertension (r2=0.92; p<0.001), heart failure (r2=0.97; p<0.001), cerebrovascular illnesses (r2=0.896; p<0.001) and stability for angina (r2=0.24; p=0.148). Similar trends were reported for males (r2=0.94; p<0.001) and females (r2=0.97; p<0.001) for the four cardiovascular diseases, with higher mean rates for males (126.07) in 10,000 inhabitants, with hospitalization and model rates showing differences between the gender for HAS, cerebrovascular diseases and angina. A significant decrease in hospitalization rates occurred in the four age groups for males and females. Mean hospitalization rates were higher for males with a lower decrease rate in all age groups. Expansion of FHS coverage in the state of Paraná increased and hospitalization in most regional health units decreased during the period analyzed . There was a proportionally inverse co-relationship of hospitalization rates by CCSAP and FHS coverage by the state of Paraná (r=-0.91; p<0.001) and for all regional health units. Results showed a decreasing trend in hospitalization rates due to cardiovascular conditions sensitive to primary health care in the state of Paraná, Brazil, for most causes, gender and age. Rates were also strongly and inversely co-related to FHS population coverage for the state as a whole and for most of the regional health units. Results strengthen indication for sensitive condition as an epidemiological tool to monitor cardiovascular diseases at primary health level and strengthen the hypothesis that a strong, equanimous and universal primary health care impacts determinants of cardiovascular diseases. The above may be observed in the hospitalizations due to the illness and suggests that there are different accesses to cardiovascular health care in the regional units affected by several factors which overall determine that people aged 35 - 74 years in the state of Paraná are healthier.